KAJIAN EMPIRIS KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR DI BEI - Muhammad Fahmi; Rahmawati Hanny Yustrianthe (Optimum: Jurnal Ekonomi dan Pembangunan, 2015)
This study aimed to analyze the factors that affect the debt policy on companies listed in Indonesia Stock Exchange in the year 2011-2013. The sampling technique is done by using purposive sampling. The sample in this study as many as 34 companies listed in Indonesia Stock Exchange. Data analysis began with descriptive statistical test, followed by the normality of the data, the classical assumption test, and regression analysis. The results of this study indicate that partial insider ownership structure, a set of investment opportunity, asset structure, and free cash flow do not affect debt policy. Only the size of the company and partially affecting profitability debt policy. Insider ownership structure, a set of investment opportunity, asset structure, the size of the company, free cash flow and profitability simultaneously affect the debt policy.